FAKTOR-FAKTOR YANG MEMENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN - Sarwono Budiyanto; Elma Muncar Aditya (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
This study aimed to examine debt to equity, profitability, ownership structure, firm size, auditor quality and auditor switching on timeliness of the submission of the financial statements. The samples in this study were food and beverage companies listed in Indonesia stock exchange during 2010-2012 amounts to 46 data. The data were analyzed by logistic regression analysis. Research results showed that auditor switching had significant influence on timeliness of financial statements. While debt to equity, ownership structure, firm size, profitability, and auditor quality had no effect on timeliness of financial statements.